Synthesis of 1,4- and 1,3-Bis-(5-Alkylthio-1,3,4-Oxadiazol-2-yl) Benzenes - Tashtoush, Hasan; Bataineh, Sameer; Al-Talib, Mahmoud (Asian Journal of Chemistry, 2010)
1,4- and 1,3-Benzene dicarboxylic acid dihydrazides reacted with carbon disulfide in basic medium to afford bis-(5-mercapto-1,3,4-oxadiazol-2- yl) benzenes, 2a, b. The latter compounds were alkylated by the reaction with alkyl halides in basic medium. The reaction of 1,2-benzene dicarboxylic acid dihydrazide under similar conditions was accompanied with unexpected rearrangement.